Pengaruh Model Pembelajaran Problem Based Learning dan Gaya Kognitif Terhadap Hasil Belajar IPA Siswa di Kelas VII MTSN 2 Tanjung Jabung Timur: Effect of Problem Based Learning Model and Cognitive Styles on Science Learning Outcomes in Class VII of MTSN 2 Tanjung Jabung Timur - Sartika Sepriyani; Rayandra Asyhar; Asrial Asrial (Universitas Jambi, 2018)
The ability to solve problems is a skill that students need to have in dealing with various problems in life. This study aims to determine the effect of problem based learning models; cognitive styles and interaction between both factors on science learning outcomes of students in class VII of MTs 2 Tanjung Jabung Timur in academic year 2015/2016. This research was conducted with a quasi-experimental research method by applying a 2 × 2 factorial design. The study sample consisted of an experimental class of 30 students and a control class of 29 students. Data collection was conducted using two types of instruments, namely the Group Embedded Figures Test (GEFT) to measure students cognitive styles and students' learning outcomes test in essay forms. The Problem Based Learning model affect the learning outcomes, there is significant difference in science learning outcomes between students who have Cognitive field dependent (FD) style that is taught by the Problem Based Learning model and students who have Cognitive FD style that is taught by conventional learning models. The results show that the value of the experimental class post-test is higher than that of the control class. In short, the experimental class with the application of the Problem Based Learning model in the learning process provides higher learning outcomes than that of the conventional models.